Visual recovery comes after anatomical recovery after intravitreal aflibercept treatment in macular edema secondary to branch retinal vein occlusion - Alper Halil Bayat; Burak Erden; Akin Cakir; Seyma Gulcenur Ozturan; Selim Bolukbasi; Mustafa Nuri Elcioglu (Medicine Science, 2018)
To determine the time of anatomical and visual responses of intravitreal aflibercept (IVA) injections in patients with naive macular edema (ME) due to branch retinal vein occlusion (BRVO). 54 eyes of 54 patients who had three IVA injections after BRVO were retrospectively studied. All of the patients had three monthly IVA injections. SD-OCT was performed at the initial visit and one month after every injection. Changes in central macular thickness (CMT), best corrected visual acuity (BCVA) were determined. Results: 28 of 54 patients were women and 26 of 54 patients were man. Mean age was 62.56±2.35 years. Mean BCVA of the patients was logMAR 1.00±0.13 and the mean CMT was 476±35 µm. After first injections; mean BCVA and CMT were improved to logMAR 0.73±0.19, 279±15 µm respectively. These improvements were statically significant (p=0.047 and p=0.000 respectively). After second injections there was not any improvement in BCVA or CMT. The mean BCVA logMAR 0.75±0.18 and mean CMT 279±10 µm (p=0.725 and p=0.991). After third injections mean CMT was 267±6 µm and mean BCVA was logMAR 0.58±0.15. Although after third injections, CMT did not change but BCVA was statically significant improved (p=0.77 and p=0.036 respectively). Visual recovery comes after anatomical recovery after intravitreal aflibercept injections in patients with naive ME due to BRVO. [Med-Science 2018; 7(4.000): 810-2]